Popularizing diversity for children in videos on YouTube - Turnbull, Judith (Jan Kochanowski University Press, 2022)
The study analyzes how information about diversity is conveyed to young people. It is a question that children, even from an early age, will most likely come face to face with either personally or indirectly, at school or in their neighbourhood. As members of society, albeit currently “junior” members, children need to understand and embrace diversity to become responsible citizens now and in the future. The analysis is based on a corpus of videos from YouTube and adopts an eclectic, qualitative approach to capture the various facets of popularization for children, in both its cognitive and communicative dimensions, also in view of the fact that communication with children needs to be ageappropriate, thus requiring different communicative strategies for different age groups (Kolucki – Lemish 2011). The study also briefly takes into consideration the multimodal elements of the videos that are used to enhance the presentation and understanding of information.